Development of puzzle-based learning to improve science learning outcomes of Indonesian geographic conditions for fifth-graders - Dinda Tiara Arbai; Fitria Dwi Prasetyaningtyas (Universitas Muhammadiyah Malang, 2024)
The lack of teacher ability to develop technology-based learning media and the lack of interaction in science and science learning activities result in less interesting learning and low student learning outcomes. This research aimed to develop learning puzzle media to determine its feasibility and effectiveness. The type of research used is research and development or Research and Development (R&D) which uses the research model design from Borg and Gall. There is a media and material validation process by expert lecturers. The subjects in this study were grade 5 students of Sekaran 01 State Elementary School, in the small-scale test there were 6 and in the large-scale test there were 20. The research method applied is the media development method, with data collection techniques that include observation, interviews, questionnaires, tests, and documentation. The research results show that material experts rate validation at 92%, and media experts rate it at 86%. The results of the n-gain trial obtained a cognitive n-gain score of 0.3030, with an average difference of 12. So, the n-gain score on the cognitive pretest and posttest learning outcomes on the large-scale trial was at a medium level, with a level of effectiveness amounting to 30.3030. The average increase shows that learning uses learning puzzles. Future research is expected to apply the media to simpler devices that can be used in a variety of classroom situations and have an easy-to-use and attractive appearance.